The Effect Of Price, Promotion, And Trust On Product Purchase Decisions On The Shopee Marketplace - Hutauruk, Basar Maringan; Soejarminto, Yos (LPPJPHKI Universitas Dehasen Bengkulu, 2025)
This study aims to determine the Effect of Price, Promotion, and Trust on Product Purchase Decisions on the Shopee Marketplace, this research method is a quantitative type of population in this study are Students of Pelita Bangsa University Faculty of Economics and Business class of 2017 who have transacted on the Shopee marketplace, researchers used a Proportional Random Sampling sampling technique totaling 95 people. The data taken in this study used a questionnaire method. Instrument testing in this study used a validity test, reliability test, and analysis method using multiple linear tests with a coefficient of determination test (R2), t test, and f test. This study used the help of the SPSS version 23 application. The results of this study indicate that the price variable does not have a partial effect on product purchase decisions on the Shopee marketplace, this is proven by the t test. while the promotion variable and the trust variable have a positive and significant partial effect on the product purchasing decision variable on the Shopee Marketplace. The price, promotion, and trust variables have a simultaneous effect. This is proven by the f test conducted by the researcher where the calculated f value is greater than the f table, namely 49.046> 3.097 and a significance value of 0.000 <0.05, and the results of the determination coefficient test (R2) obtained a percentage of 60.5% of the Purchase Decision variable influenced by the Price, Promotion, and Trust variables, while 38.2% is influenced by other variables not explained in this study.